An Exhaustive Review on State-of-the-art Techniques for Anomaly Detection on Attributed Networks - et. al., Wasim Khan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Social Network sites are one of the most prominent websites used in almost every facet of life. A social network reflects relationships among social entities, including acquaintances, co-workers, or co-authors. With the extreme success of Social networks, the misuse has also been escalated and unlocked the way for various illegal behavior and security threats. Social Network anomaly detection has become a critical topic to be explored by researchers. The nature of the input data is a significant aspect of an anomaly detection technique. In the field of anomaly detection in the social network, input networks can be classified as static or dynamic, Attributed or unattributed. The number of nodes and the connections between the nodes in static networks would not change with time. Attribute networks are pervasive in various domains and constitute a vital element of modern technological architecture, where node attributes support the topological structure in data exploration. While social networks build up over time, evaluating them as if they had been static is very beneficial. Numerous studies have been done for Anomaly detection, but to the best of our knowledge, research in static attributed anomaly detection has been very limited. This review tries to portray earlier research on detecting anomalies for social static attributed networks and thoroughly discusses state-of-the-art embedding approaches